Biofixation of Carbon dioxide by Chlamydomonas sp. in a Tubular Photobioreactor - Hadiyanto, H; Sumarno, S; Nur Rostika, Rufaida; Abyor Handayani, Noer (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
The biogas production from anaerobic digestion is a potential fuel for power generators application, if biogas can be upgraded to the same standards as fossil natural gas by CO2, H2S, and other non-combustible component removal. Microalgae Chlamydomonas sp. has potency to biofix the carbon dioxide and can be used as an additional food ingredient. The variations of flow rate and carbon dioxide concentration in the process resulting different value of biomass production and carbon dioxide biofixation. Biomass production at 40% carbon dioxide concentration obtained 5.685 gr/dm3 at 10% carbon dioxide concentration obtained 4.892 gr/dm3. The greatest value of carbon dioxide absorption occurs at a 40% concentration amounting to 12.09%. The rate of growth and productivity of microalgae tend to rise in 10% and 20% (%v) carbon dioxide concentration, but began started a constant at 30% and 40% (%v) carbon dioxide concentration. Biomass production tends to increase in light conditions while a constant in dark conditions. This study used Chlamydomonas sp. as media culture and performed on bubble column and tubular reactor with 6 litres of culture medium at a temperature of 28oC and atmospheric pressure.